Por el sendero del huerto”: de las patologías de la investigación y sobre el “progreso” del conocimiento - Fernández Mcclintock, James W. (Revista de Antropología Social, 2006)
This essay evokes various field materials to treat of two tropes, the Path and the Garden. The first is the primordial and widely persistent and still present trope of hunters and gatherers and the second is the trope of a later stage in the evolution of culture, the trope of horticulturalists, agriculturalists and of “the civilized” whose “civilizations” the progressive subordinations of nature, horticulture and agriculture, have made possible. These tropes are at play, that is to say they interact in various ways particularly in the notion of the Garden Path and of the irrigated and plotted, that is to say path organized fields of agricultural cultivation. We will speak of path-ology, a coinage that has two meanings 1. the study of the logic of the path trope and 2. the ever possible over commitment to path-like thinking in inquiry. In addition to field materials from the author and from Africanist colleagues, particularly Victor Turner, we will treat of the presence and effect of these tropes in contemporary evolutionism, environmentalism and industrial capitalism. The presence of the field path trope in anthropological field work and the path dependency trope in social history will be treated. We will reflect, as may the reader in Spain and as did Saint Teresa in her “Path of Perfection”, Camino de Perfección, on the pilgrimage of life and more especially on the Pilgrimage to Santiago, an important and singularly identifying and potentially fulfilling elaboration in Christendom of the path trope, so otherwise ever-present in Salvationist and Perfectionist religious argument but, presently in late capitalism, so politically and commercially useful.